EMOTIONAL STATES OF ELDERLY WOMEN WITH ISCHEMIC HEART DISEASE AS A COMPLEX PERSONALITY PHENOMENON - Oniskovets, Bogdana (PSYCHOLOGICAL JOURNAL, 2020)
The article examines emotional states of elderly people with ischemic heart disease (IHD) as a complex personality phenomenon. An individual’s emotional experience is manifested in different emotions, feelings and emotional states, which are evaluative and have negative/positive poles. The main purpose of this work was to analyse theoretically the emotional states of elderly people with ischemic heart disease as a complex personality phenomenon that has mental, psychophysiological and behavioural levels. We have determined theoretically that negative feelings worsen a functional state of the heart, causing its electromagnetic destabilization. The main mechanisms of the pathogenic influence of stresses on IHD are: the increased release of catecholamines, which leads to increased myocardial oxygen consumption as a result of an increased heart rate, higher blood pressure and stronger myocardial contraction force; a violated vascular tone of the epicardial arteries and worsened microcirculation; increased platelet aggregation, secretion of certain blood coagulation factors, decreased fibrinolytic activity of the blood. Considering the problem of negative emotional states, the scientific literature notes the following states that characterize an individual in difficult life situations: anxiety, depression, asthenia, hostility. Long-term emotional overstrain, acute and chronic traumas of the psyche, psychological-emotional disorders, the most significant of which are depressive and anxiety-phobic, influence significantly on older women’s ischemic heart disease. In addition, at the case of depression, behavioural factors such as patients’ reluctance to take medications or to comply with the prescribed regimen have a significant effect. The article determines that elderly women’s emotional states are mainly negative, they are caused by chronic emotional stresses, emotional overstrain (distress) and psychological-emotional disorders and increases the risk of coronary heart disease.